Implementation of Health Counseling on Diarrhea in Children at Sdn 08982 Batu Dua Puluh, Panei District, Simalungun Regency - Br Saragih, Jumadiah Wardati; Marbun, Meyana (PT Inovasi Pratama Internasional, 2022)
Diarrhea is a very common condition. It can affect both children and adults. The highest incidence is found in children under 2 years of age, where viruses are the most common cause. Diarrhea is defined as an increase in the frequency and looseness of bowel movements. A normal frequency of bowel movements is 1-3 times per day and a volume of 200-300 ml. 250 grams a day. If it exceeds that amount, then a person can be said to have diarrhea. There are several terms for diarrhea, namely: Acute diarrhea if it lasts less than 1 week; Persistent diarrhea is diarrhea that lasts more than 14 days and is caused by an infection, for example, diarrhea caused by a virus due to poor implementation so that it continues for more than 14 days, dysentery that is not treated so that it lasts more than 14 days, or diarrhea caused by bacteria that are resistant to a number of antibiotics so that it lasts more than 14 days; Chronic diarrhea is diarrhea that lasts more than 14 days and is not caused by a virus, for example due to impaired intestinal function in digesting food, the presence of a food substance that cannot be absorbed by the body, and so on; Dysentery is diarrhea accompanied by mucus and blood. Dysentery is caused by the Shigella bacteria or the Entamoeba histolotica parasite; Cholera is watery diarrhea in which almost no stool residue can be found at all (watery diarrhea). Cholera often causes epidemics and very quickly causes dehydration which causes the sufferer to die. Cholera is caused by the bacteria Vibrio cholerae.